Long time behavior of a degenerate NPZ model with spatial heterogeneity. (October 2022) - Cheng, Hongyu; Lv, Yunfei; Yuan, Rong
Abstract: This work proposes a nutrient–phytoplankton–zooplankton (NPZ) model which is governed by a partially degenerate reaction–diffusion equation. Due to the noncompactness of solution map, the Kuratowski measure is introduced to prove the existence of the global attractor. By an innovative construction of Lyapunov functions, sufficient conditions are given to obtain the global attractivity of steady states of the system with spatial parameters.